Analyses and modeling of the 12CH4 spectrum at 80 K between 6539 and 6800 cm−1. (January 2016) - Nikitin, A.V.; Rey, M.; Tashkun, S.A.; Kassi, S.; Mondelain, D.; Campargue, A.; Tyuterev, Vl.G.
Abstract: Accurate rovibrational analysis of the lower part of the Icosad 12 CH4 spectrum in the 6539–6800 cm −1 region is reported. The analysis uses the WKLMC experimental line list previously obtained in Grenoble by Cavity Ring Down Spectroscopy and Differential Absorption Spectroscopy at T =80 K. Based on an ab initio potential energy surface, the full Hamiltonian of methane nuclear motion was reduced to an effective Hamiltonian using high-order Contact Transformations method with a subsequent empirical optimization of parameters. About 2445 experimental line positions were fitted with RMS standard deviations of 0.005 cm −1 and 1644 line intensities were modeled using effective dipole moment with the RMS deviation of 11.5%. Twenty five vibrational energy levels of the lower part of the Icosad were determined. Highlights: 12 CH4 line list at 80 K is theoretically modeled in the 6439–6800 cm −1 region. 2443 experimental line positions are reproduced with a 0.005 cm −1 rms . 1644 experimental line intensities at 80 K are modeled with 11% rms. The list of assigned lines with intensities at 80 K is provided. 25 Vibrational energy levels of the lower part of the Icosad are determined.